2010
DOI: 10.1007/s10707-010-0104-5
|View full text |Cite
|
Sign up to set email alerts
|

OCL for formal modelling of topological constraints involving regions with broad boundaries

Abstract: Integrity constraints can control topological relations of objects in spatial databases. These constraints can be modelled using formal languages such as the spatial extension of the Object Constraint Language (Spatial OCL). This language allows the expression of topological integrity constraints involving crisp spatial objects but it does not support constraints involving spatial objects with vague shapes (e.g. forest stand, pollution zone, valley or lake). In this paper, we propose an extension of Spatial OC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 26 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…Nevertheless, to the best of my knowledge, the Object Constraint Language (OCL) [216] has the potential to implement the formal theory presented in this chapter and to formalize map specifications together with a UML model. Research in the geospatial domain has demonstrated the use of OCL and UML in modeling topological rules in spatial databases [25] and specifications for multiple representation databases and generalization [61,69,71,194].…”
Section: Implementation Of the Theorymentioning
confidence: 99%
“…Nevertheless, to the best of my knowledge, the Object Constraint Language (OCL) [216] has the potential to implement the formal theory presented in this chapter and to formalize map specifications together with a UML model. Research in the geospatial domain has demonstrated the use of OCL and UML in modeling topological rules in spatial databases [25] and specifications for multiple representation databases and generalization [61,69,71,194].…”
Section: Implementation Of the Theorymentioning
confidence: 99%